Effect of wound protectors on surgical site infection in patients undergoing whipple procedure. Issue 8 (August 2021) - Tee, May C.; Chen, Leo; Franko, Jan; Edwards, Janet P.; Raman, Shankar; Ball, Chad G.
Abstract: Background: Conflicting data persists for use of wound protectors in pancreatoduodenectomy (PD) to prevent surgical site infection (SSI). We aimed to examine, at a multi-institutional level, the effect of wound protectors on superficial or deep SSI following elective open PD. Methods: The American College of Surgeons National Surgical Quality Improvement Program pancreatectomy procedure targeted participant use file was queried from 2016 to 2018. Planned open PD procedures were extracted. Univariable, multivariable, and propensity score matched analyses were conducted. Results: 11, 562 patients undergoing PD were evaluated, 27% of which used wound protectors. Wound protectors decreased superficial or deep SSI risk in all patients (5.7% vs. 9.5%, P < 0.001), patients who have (6.6% vs. 12.2%, P < 0.001) and who did not have (4.6% vs. 6.5%, P = 0.011) a biliary stent. Propensity score matched analysis confirms such results (OR = 0.56, 95% CI: 0.46–0.69, P < 0.001 overall, OR = 0.66, 95% CI: 0.46–0.95, P = 0.03 without biliary stent, OR = 0.57, 95% CI: 0.44–0.73, P < 0.001 with biliary stent). Conclusions: Wound protectors reduce risk of superficial or deep SSI in patients undergoing PD, yet only a quarter of PD were associated with their use. This protective effect is seen whether patients have or have not had preoperative biliary stenting.